Morphological and Growth Study of Three Edible Clam Species in Sayung, Demak: - Taqiyya Hikma Rodhiyya; Delianis Pringgenies; Dwi Haryanti (Masyarakat Moluska Indonesia, 2026)
Mollusks are valuable aquatic biological resources widely consumed by coastal communities.This study aims to characterize the morphology and size of edible mollusks collected from local middlemen in the waters of Sayung, Demak. The research includes morphological identification, measurement of body dimensions (length, width, height, and weight), analysis of size variation among species, and the relationship between morphology and commercial potential. Samples were obtained from local collectors and analyzed through taxonomic identification and morphometric measurements. Three species were identified: Anadara granosa (blood cockle), Perna viridis (green mussel), and Amusium pleuronectes (fan shell), with A. granosa being the most abundant (383 individuals), followed by P. viridis (331 ) and A. pleuronectes (191 ). Size measurements varied, with lengths ranging from 1.54–8 cm, heights from 1.048–9.7 cm, widths from 0.72–7.492 cm, and weights from 3.75–41.57 grams. Statistical analysis revealed that all three species exhibited negative allometric growth (b<3) in the length–weight and width–weight relationships, meaning that increases in size were not proportional to increases in weight. However, A. pleuronectes showed positive allometric growth (b>3) in the height–weight relationship, indicating that height contributed disproportionately more to body mass. These findings suggest varying commercial potential across species, with A. granosa being the most abundant and consistently within marketable size. The data serve as a valuable basis for sustainable mollusk resource management in the Sayung coastal area of Demak.